Digestive and appendicular soft-parts, with behavioural implications, in a large Ordovician trilobite from the Fezouata Lagerstätte, Morocco - Gutiérrez-Marco, Juan C. (Sci Rep, 2017)
Trilobites were one of the most successful groups of marine arthropods during the Palaeozoic era, yet their soft-part anatomy is only known from a few exceptionally-preserved specimens found in a handful of localities from the Cambrian to the Devonian. This is because, even if the sclerotized appendages were not destroyed during early taphonomic stages, they are often overprinted by the three-dimensional, mineralised exoskeleton. Inferences about the ventral anatomy and behavioural activities of trilobites can also be derived from the ichnological record, which suggests that most Cruziana and Rusophycus trace fossils were possibly produced by the actions of trilobites. Three specimens of the asaphid trilobite Megistaspis (Ekeraspis) hammondi, have been discovered in the Lower Ordovician Fezouata Konservat-Lagerstätte of southern Morocco, preserving appendages and digestive tract. The digestive structures include a crop with digestive caeca, while the appendages display exopodal setae and slight heteropody (cephalic endopods larger and more spinose than thoracic and pygidial ones). The combination of these digestive structures and the heteropody has never been described together among trilobites, and the latter could assist in the understanding of the production of certain comb-like traces of the Cruziana rugosa group, which are extraordinarily abundant on the shallow marine shelves around Gondwana.